La focalización y lo real extraño en la cuentística de Lino Novás Calvo. - Caner Camejo, Asbrúbal. (University of Ottawa (Canada), 2002)
Lino Novas Calvo (1905--1983) was an outstanding Cuban short-story writer and a pioneer in the modern narrative in his country. I consider point of view as a web of stances that the narrator takes vis-a-vis his narrative world---mainly perceptual and phraseological stances---made possible by a certain status of the narrator, and semiosically contributing to the expression of an ideological stance attributable to the implied or inferred author. My thesis concentrates on the perceptual stance or focalization in three of the most characteristic short stories by Novas Calvo---"La noche de Ramon Yendia", "Cayo Canas" and "La vision de Tamaria"---this stance constituting the central one in the functioning of point of view in Novas Calvo's narrative; the main focus of this stance is triple: character, space and time, and it often produces sequences of a cinematic kind. I also pay close attention to the modes of phraseological stance that generate the principal perceptual-stance phenomenon, namely the mediation of focalization. Coupled to these techniques, I examine the role of Cuban and popular language as well as poetic language. (Abstract shortened by UMI.)
Keywords: Literature, Latin American.